2019
DOI: 10.1111/jgh.14901
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of risk scoring systems in predicting endoscopic treatment in colonic diverticular bleeding

Abstract: Background and Aims:The identification of stigmata of recent hemorrhage (SRH) in colonic diverticular bleeding (CDB) enables an endoscopic treatment and can improve the clinical outcome. However, SRH identification rate remains low. This study aims to investigate whether NOBLADS and Strate scoring systems are useful for predicting SRH identification rate of CDB pre-procedurally via colonoscopy. Methods: In this single-center retrospective observational study, 302 patients who experienced their first episode of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…Although the number of patients was limited, and the study was retrospective and was performed at a single center without a control group, we showed that OS-1 Jelly injection is a useful technique for difficult situations. Oguri et al reported the relatively equal distribution of SRH as follows: AB, 34.9%; NBVV, 32.5%; and AC, 32.5%; this meant that 65% of stigmata were NBVV and AC [ 12 ]. Thus, improvement of NBVV and AC detection rate should be considered as the key for CDB management.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the number of patients was limited, and the study was retrospective and was performed at a single center without a control group, we showed that OS-1 Jelly injection is a useful technique for difficult situations. Oguri et al reported the relatively equal distribution of SRH as follows: AB, 34.9%; NBVV, 32.5%; and AC, 32.5%; this meant that 65% of stigmata were NBVV and AC [ 12 ]. Thus, improvement of NBVV and AC detection rate should be considered as the key for CDB management.…”
Section: Discussionmentioning
confidence: 99%
“…Oguri et al reported the relatively equal distribution of SRH as follows: AB, 34.9%; NBVV, 32.5%; and AC, 32.5%; this meant that 65% of stigmata were NBVV and AC. 12 Thus, improvement of NBVV and AC detection rate should be considered as the key for CDB management. By applying the gel immersion method, we considered that the detection of SRH would improve and the rate of re-bleeding and readmission would decrease.…”
Section: A B Cmentioning
confidence: 99%
See 3 more Smart Citations